Larvae of gryporhynchid cestodes (Cyclophyllidea) from fish: a review - Scholz, Tomás; Bray, Rodney A; Kuchta, Roman; Repová, Radmila (Folia parasitologica, 2004)
Larvae (metacestodes) of tapeworms of the cyclophyllidean family Gryporhynchidae (previously included in the Dilepididae) occur in different internal organs of fresh- and brackish water fish (110 fish species of 27 families in 12 orders reported), which serve as the second intermediate hosts. The species composition, spectrum of fish hosts, sites of infection, and geographical distribution of gryporhynchids recorded from fish are reviewed here on the basis of literary data and examination of extensive material from helminthological collections. Metacestodes of the following genera have been found in fish: Amirthalingamia Bray, 1974 (1 species), Ascodilepis Guildal, 1960 (1), Cyclustera Fuhrmann, 1901 (4), Dendrouterina Fuhrmann, 1912 (1), Glossocercus Chandler, 1935 (3), Neogryporhynchus Baer et Bona, 1960 (1), Paradilepis Hsü, 1935 (5), Parvitaenia Burt, 1940 (2), and Valipora Linton, 1927 (3). However, most published records concern only three species, namely Neogryporhynchus cheilancristrotus (Wedl, 1855) from the intestinal lumen, Paradilepis scolecina (Rudolphi, 1819) from the liver and mesenteries, and Valipora campylancristrota (Wedl, 1855) from the gall bladder of cyprinids and other fish in the Palaearctic Region. Data on other species as well as reports from other regions are very scarce and almost no information is available from Australia, tropical Asia and South America. A recent study of gryporhynchid metacestodes from Mexico (Scholz and Salgado-Maldonado 2001), which reported 13 species, suggested that they may be more common than indicated by records in the literature. Although only a few cases of pathogenic influence of larvae on fish hosts have been reported, the veterinary importance of gryporhynchids remains to be assessed on the basis of more detailed studies. The data available indicate a strict host and site specificity of some species whereas others occur in a wide spectrum of fish hosts and are not strictly site-specific. Evaluation of Paradilepis larvae from the liver of salmonid fish from British Columbia, Canada, identified as P. simoni Rausch, 1949 by Ching (1982), has shown that they probably belong to two species, P. simoni and P. rugovaginosus Freeman, 1954. Metacestodes of the latter species and those of Cyclustera magna (Baer, 1959) from the intestinal wall of Tilapia zillii (Gervais) from Kenya are reported from fish for the first time.
Keywords: Cestoda; ryby; Fishes; druhová specificita; Larva; larva; Animals; Species Specificity; zeměpis; Host-Parasite Interactions; Geography; zvířata; interakce hostitele a parazita